Parent and teacher perspectives in collaborative concepts of therapeutic programs for students with ADHD. Issue 4 (1st October 2016) - Chaimaha, Napalai; Chinchai, Supaporn
ABSTRACT: The purpose of this study was to explore parents' and teachers' perspectives in collaborative concepts of therapeutic programs for students with ADHD. The qualitative data was collected from three focus group discussions based on Future Search Conference (FSC) method, and was analyzed for themes. Participants in the separate groups—the parent group and the teacher group—identified problems in the past and current situation. Then, the mixed group created collaborative concepts of concrete action plans in the future. The core problem in the past was lack of knowledge about ADHD. At home, the parents confronted the child's academic problems and unwanted behaviors, as well as the conflict between the parents and the grandparents in the child's behavior modification. The teachers also stated many responsibilities at work and lack of collaboration between home and school were problems. For current situation, both parents and teachers informed nature of ADHD and committed to support the children more closely, although the students had not overcome academic problems yet. Finally, four themes emerged in collaborative concepts of therapeutic programs; using computer software program, a buddy system, knowledge for people relating to the students, and collaboration amongst the teachers, the parents, and the therapist.